Pro-oxidant activity of apocynin radical - Gomes Castor, Lidyane Regina [UNESP]; Locatelli, Katia Andreza [UNESP]; Ximenes, Valdecir Farias [UNESP] (Elsevier B.V., 2010)
Apocynin has been widely used as an NADPH oxidase inhibitor in many experimental models. However, concern regarding the efficacy, selectivity, and oxidative side effects of the inhibitor is increasing. In this study, our aim was to characterize the pro-oxidant properties of apocynin and the structurally-related compounds vanillin and vanillic acid. Glutathione (GSH), cysteine, ovalbumin, and the coenzyme NADPH were chosen as potential target biomolecules that could be affected by transient free radicals from apocynin, vanillin and vanillic acid. Additionally, trolox and rifampicin were used as models of hydroquinone moieties, which are particularly susceptible to oxidation. Transient radicals were generated by horseradish peroxidase/hydrogen peroxide-mediated oxidation. In the presence of apocynin, oxidation of GSH was increased seven-fold, and the product of this reaction was identified as GSSG. Similar results were obtained for oxidation of cysteine and ovalbumin. Oxidation of the coenzyme NADPH increased more than 100-fold in the presence of apocynin. Apocynin also caused rapid oxidation of trolox and rifampicin to their quinone derivatives. In conclusion, the pro-oxidant activity of apocynin is related to its previous oxidation leading to transient free radicals. This characteristic may underlie some of the recent findings regarding beneficial or deleterious effects of the phytochemical. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Apocynin; Vanillin; Vanillic acid; Pro-oxidant activity; Glutathione; Quinone; NADPH oxidase